Impact of Digital Marketing, Influencer, Live Features, and Reviews Shopee Purchase With Brand Image - Safirah, Nabilah; Anggrainie, Nova (International Journal of Economics (IJEC), 2024)
The advancement of information and communication technology in the digital era has revolutionized various aspects of human life, including in the realm of business and marketing. Marketing activities that once relied on direct interaction between sellers and buyers have now shifted towards digital marketing that utilizes online platforms. Indonesia, as the largest economy in Southeast Asia, has made an e-commerce as the main driver of socioeconomic growth. Supported by a population of over 270 million people and ever-increasing internet penetration, the development of e-commerce in Indonesia has experienced rapid progress in recent years. This study aims to analyze the impact of digital marketing, influencer marketing, live features, and Online Customer Reviews on online purchase decisions on the Shopee platform with brand Image as an intervening variable. This research used a quantitative method with a data collection technique through an online questionnaire to 210 Shopee users in Indonesia. The measurement of construct validity and reliability was carried out using the measurement model (outer model). Then, the structural model (inner model) was used to test the model's strength, predictive ability, model significance, and the direct and indirect influence of independent variables on the dependent variable. The test tool employed SmartPLS 3.0. The results of this study indicate that the variables of Digital Marketing, Live Features, and Brand Image have a significant influence on Purchase Decisions on Shopee e-commerce. Furthermore, the variables of influencer marketing, live features, and Online Customer Review have a significant influence on Brand Image on Shopee e-commerce. Meanwhile, for the indirect influence, the variable live features have a significant influence on purchase decisions on Shopee e-commerce through Brand Image as an intervening variable.